Moonwalk - Jackson, Michael, 1958-2009. (New York : Harmony Books, 2009)
Michael Jackson's only autobiography, illustrated with rare photographs from Jackson family albums and Michael's personal photographic archives, as well as a drawing done by Michael exclusively for this book.
Originally published, in slightly different form: New York : Doubleday, 1988.
Keywords: Jackson, Michael, -- 1958-2009.; Rock musicians -- United States -- Biography